Uma heurística para a programação da produção de sistemas flexíveis de manufatura usando modelagem em redes de Petri - Maggio, Eduardo Gomes Ribeiro (Universidade Federal de São Carlos, 2005)
The Petri Net based Search has been shown as a promising way to solve Flexible manufacturing Systems (FMS) Scheduling Problem. However, the response time is critical since it s a system with high computational complexity. Focusing the reduction of response time, this work proposes a heuristic for Petri Net based Search to solve FMS Scheduling problem of makespan minimization. Experiments showed improvements on response time reduction comparing with prior works
Keywords: Programação da produção; Busca heurística; Sistemas flexíveis de manufatura; FMS; Redes de Petri virtuais; Scheduling; Flexible Manufacturing System; FMS; Heuristic Search; Virtual Petri Net; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO